Neopragmatismo e religião : uma abordagem da religião como política cultural em Richard Rorty - Donadia, André Oliva (2017)
This research aims to examine the central elements of liberalism"s political philosophy and a description of what Rorty understands as justification to the defense of liberal institutions. We are going to analyze Rorty"s antifoundadionalism strategy to defend the contemporary liberal institutions. After that, we will examine Rorty"s liberal utopia. In this context, Richard Rorty argues that the religious speech is at odds with his liberal ideals. As a result, he argues, in a first moment, that religion must be privatized so that the State remains neutral. After exploring the views that constitute his choices, this dissertation shows, in particular, three of Rorty"s positions that he argues in his writings. The first argument is that religion should be privatized, the second consists in the defense of marginalization of ecclesiastics institutions and the third is that defending pragmatism is, as a result, to defend a secular liberal utopia. In this work, it will be explained how these arguments are entailed to Rorty"s commitment to his neo-pragmatism and how they fit inside this logic. We will start with a description, then it will be demonstrated that these arguments are at odds with some of “philosophical” assumptions that Rorty has made, which create practical problems that might eliminate the social ideal that Rorty designed, which creates practical problems for the social and political ideal that Rorty advocates, and finally we address a review of Rorty's position on the subject and indicate a possible inclusion of religion in public space through the notion of "literary culture."